LEMUEL GULLIVER’S SOCIAL CRITICISMS ON LILIPUT COUNTRY AS THE PORTRAYAL OF ENGLAND IN GULLIVER’S TRAVELS MOVIE - LARASMAWATI, LULUK (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keyword: criticism, sociology, cultural relativism, ethnocentrismIn the society, there are a lot of different cultures that exist. To say that a culture is correct or incorrect would imply that someone can judge the culture by their own standard of right and wrong. In cultural relativism, all points of view about the standard of culture are equal, and the truth is relative. In Gulliver’s Travels (2010) movie, Gulliver breaks the term of cultural relativism. The Liliputian’s values are not the same with Gulliver’s values as an American. Gulliver thinks that his culture is better than Liliputians, so he gives criticism on the people of Liliput country. The criticism of Lemuel Gulliver does as an American toward the life of people in Liliput country which is portrayal of England, will be main problem in this study.Sociological approach is applied in conducting this study since it focusses on Lemuel Gulliver’s social criticism on Liliput Country as the portrayal of England. To get a wider knowledge about Lemuel Gulliver’s social criticism on England the writer includes some information about American and British society at glance.This study finds that there are some criticisms that Lemuel Gulliver gives on the people of Liliputians: (1)Criticism on Liliputians’s Social Status, (2) Criticism on Liliputians’s custom marriage, (3) Criticism on Liliputians’s rigidity, and (4) Criticism on Liliputians’s architecture. The writer suggests English Department students who want to take the same material object to use other literary theory, such as feminism.